2019
DOI: 10.1002/gps.5085
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the frequency of number‐puzzle use and baseline cognitive function in a large online sample of adults aged 50 and over

Abstract: Objective Establishing affordable lifestyle interventions that might preserve cognitive function in the aging population and subsequent generations is a growing area of research focus. Data from the PROTECT study has been utilised to examine whether number‐puzzle use is related to cognitive function in older adults. Methods Data from 19 078 healthy volunteers aged 50 to 93 years old enrolled on the online PROTECT study were evaluated for self‐reported frequency of performing number puzzles. Two cognitive‐test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Unlike the SFL, the active control only had a limited number of physical exercises and did not include interactive videos, personalization, chat rooms, psycho-educational content, or virtual guide. The cognitive activities were commercially available games that did not target specific cognitive processes or strategies [25][26][27][28][29] (e.g., crossword puzzles, Sudoku, maze arcade).…”
Section: Active Control Interventionmentioning
confidence: 99%
“…Unlike the SFL, the active control only had a limited number of physical exercises and did not include interactive videos, personalization, chat rooms, psycho-educational content, or virtual guide. The cognitive activities were commercially available games that did not target specific cognitive processes or strategies [25][26][27][28][29] (e.g., crossword puzzles, Sudoku, maze arcade).…”
Section: Active Control Interventionmentioning
confidence: 99%
“…Weng et al(2021)showed that the creativity of sixth grade elementary students(121people)has a positive and signi cant effect on learning attitude and problem solving ability,as well as learning attitude on problem solving ability(P<0.05).The researchers concluded that the logical thinking puzzle game can teach and improve the students' logical thinking ability (54). Brooker et al(2019)showed that the average cognitive function scores of healthy people aged 50-93 in all areas(reasoning,focused and sustained attention,information processing,executive function,working memory and episodic memory)after playing the number puzzle game were signi cantly higher than before playing the game(P<0.0004) (55).…”
Section: Discussionmentioning
confidence: 99%
“…The participants will be trained in performing the CogTrack® System, an online set of cognitive tests with proven utility, reliability, sensitivity, and validity ( 39 ), as well as reliable sensitivity to change over time ( 40 ); (see later). The battery of tests includes previously described tests, such as simple reaction time, choice reaction time, digit vigilance, immediate and delayed word recall and recognition, pattern separation, spatial working memory, and numeric working memory ( 41 ). The baseline test will be performed at home on two occasions before taking the first study dose and then monthly for 6 months.…”
Section: Methodsmentioning
confidence: 99%